Clinical evaluation of Helioseal F fissure sealant - Koch, Martin Jean; García-Godoy, Franklin; Mayer, Thomas; Staehle, Hans Jörg (Clinical oral investigations, 1998)
Unfilled resins are commonly in use as sealant material. In addition, there are filled sealants available. Helioseal F is a newly developed filled material with fluoride release. In this clinical trial, Helioseal F has been evaluated in one lower molar versus Delton opaque as an unfilled control in lower molars. After 12 months there were no significant differences in retention, porosities, and the number of clinically unacceptable margins between the materials. The complete retention was 30 out of 31 examined teeth for Delton and 28 out of 31 for Helioseal F. After 1 year of clinical testing, these results indicate that a sealant containing fluoride-releasing particles did not show a significant difference in retention rate compared to an unfilled conventional sealant. However, long-term results concerning marginal adaptation should be evaluated.